Women of the Roman ruling class at the beginning of the Imperial Period - الخطيب, ايفا (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Roman ruling class women played a major role in changing the events and course of Roman History And contributed to the man s side as a wife and as a mother in making great changes and accomplishing achievements , she played a role no less important that of a man in managing affairs in the political and military arena with intelligence and cunning that is no less than that of a man s intelligence and savvy , if not superior his intelligence in many cases using all possible and available means and methods to obtain her desire to strengthen the influence and power of her husband or her son the Emperor and eliminate his opponents , she could control and interfere in all the big and small matters